2009
DOI: 10.1177/1557988309357232
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Dual Task Gait Performance in Older Adults

Abstract: Although attention-dividing dual tasks hinder gait performance in older persons, gender differences in gait have not been examined. The purpose of this study was to examine whether gait performance differs between older men and women during dual task walking. A total of 44 healthy adults (20 men and 24 women) aged 65 years or older participated in the study. Participants walked under normal and dual task (backward spelling) conditions at self-selected speeds. Mean gait speed and stride-to-stride variability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 44 publications
1
46
3
2
Order By: Relevance
“…Of these, 13 analyzed a single group of elderly individuals [25][26][27][28][29][30][31][32][33][34][35][36][37] and 15 compared groups of elderly individuals with different characteristics. 5,6,[16][17][18][19][20][21][38][39][40][41][42][43][44] Charts 1 and 2 contain the details of the studies included in this review, as well as the details of the samples, instruments, tasks and spatial and temporal parameters of gait in each study. Step time; variability of the step …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 13 analyzed a single group of elderly individuals [25][26][27][28][29][30][31][32][33][34][35][36][37] and 15 compared groups of elderly individuals with different characteristics. 5,6,[16][17][18][19][20][21][38][39][40][41][42][43][44] Charts 1 and 2 contain the details of the studies included in this review, as well as the details of the samples, instruments, tasks and spatial and temporal parameters of gait in each study. Step time; variability of the step …”
Section: Resultsmentioning
confidence: 99%
“…17,[29][30][31][33][34][35]37 One study reported no alteration in the parameter during the DT. 25 Of the 10 studies that compared two groups of elderly individuals with different characteristics, six indicated a reduction in gait speed among fallers, 31,42,44 recurrent fallers 5 and those who feared falling 18,43 during a DT with an arithmetic CT, a verbal fluency CT, a motor task (MT) and a TT. The other four studies used a DT with an arithmetic CT, a verbal fluency CT and an executive function CT and found no significant effect on gait speed.…”
Section: Speedmentioning
confidence: 99%
See 2 more Smart Citations
“…142 marcha (MENZ; FITZPATRICK, 2003;TALBOT et al, 2005;BAIRD;RICHARD, 2009;YOUDAS;LANZINO, 2009). Deste modo, desafios cotidianos durante a marcha, podem comprometer seriamente a capacidade de controlar o equilíbrio dinâmico (PIJNAPPELS; BOBBERT; VAN DIEEN, 2001;CHOU, 2005;PIJNAPPELS, 2008).…”
unclassified